Bridging the gap: bioinspired robotics as catalyst for interdisciplinary education - Cayetano-Jiménez, Israel Ulises; Bustamante-Bello, Rogelio; Ramírez-Cadena, Miguel (Frontiers in Education, 2024)
In the current educational landscape, prioritizing interdisciplinary skills and sustainable innovation is key. This study explores the impact of an innovative pedagogical approach that combines biology with engineering. Undergraduate students at Tecnol ógico de Monterrey in Mexico City engaged in creating bioinspired robots for real-world applications. Two teams concentrated on developing robots for post-earthquake search and rescue, while two additional teams focused on wildlife observation. These projects were based on initial workshops that covered animal biomechanics, soft robotics, and neuroscience. The project culminated in functional robotic prototypes, reflecting the success of this cross-disciplinary educational model.Post-project assessments revealed a marked increase in students' skills in both biological understanding and robotic design, underscoring the transformative potential of integrating diverse fields of study. This experimental curriculum demonstrates that combining traditional knowledge with technological innovation through digital platforms and open innovation significantly enhances learning outcomes. The study presents a compelling case for educational strategies that foster analytical reasoning, empathy, and emotional literacy, alongside scientific acumen. It offers insights for educators and policymakers into the benefits of merging biology, robotics, and education, promoting a model that prepares students as holistic thinkers and versatile innovators for future challenges.